2013
DOI: 10.1172/jci63324
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral stress accelerates prostate cancer development in mice

Abstract: Prostate cancer patients have increased levels of stress and anxiety. Conversely, men who take beta blockers, which interfere with signaling from the stress hormones adrenaline and noradrenaline, have a lower incidence of prostate cancer; however, the mechanisms underlying stress-prostate cancer interactions are unknown. Here, we report that stress promotes prostate carcinogenesis in mice in an adrenaline-dependent manner. Behavioral stress inhibited apoptosis and delayed prostate tumor involution both in phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
215
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(233 citation statements)
references
References 59 publications
(68 reference statements)
14
215
2
2
Order By: Relevance
“…potentiate the proliferation and migration of the cancer cells, inhibit the tumor cell apoptosis, increase the tumor cell invasiveness and metastatic activity, support the neoangiogenesis in the tumor tissue, or suppress the natural killer cell activity (Godbout and Glaser 2006;Sood et al 2006;Th aker et al 2006;Andersen et al 2007;Sephton et al 2009;Hassan et al 2013;Nagaraja et al 2013). Th ese eff ects are mediated especially by neurotransmitters released by sympathetic nerve endings, particularly by norepinephrine (Yang 2010).…”
mentioning
confidence: 99%
“…potentiate the proliferation and migration of the cancer cells, inhibit the tumor cell apoptosis, increase the tumor cell invasiveness and metastatic activity, support the neoangiogenesis in the tumor tissue, or suppress the natural killer cell activity (Godbout and Glaser 2006;Sood et al 2006;Th aker et al 2006;Andersen et al 2007;Sephton et al 2009;Hassan et al 2013;Nagaraja et al 2013). Th ese eff ects are mediated especially by neurotransmitters released by sympathetic nerve endings, particularly by norepinephrine (Yang 2010).…”
mentioning
confidence: 99%
“…A recent study has also shown that in mouse models of prostate cancer, immobilisation stress and systemic adrenaline promote prostatic intraepithelial neoplasia (PIN) and resistance of tumours to apoptosis normally induced by the PI3K inhibitor ZSTK474. 7 Unlike studies based on tumour xenografts in the flank of immunocompromised mice, the work described by Magnon et al 8 employed orthotopic injection of human PC-3 prostate cancer cells directly into the ventral prostate gland, mirroring the tumour microenvironment found in human disease. The PC-3 cells were labelled with luciferase so that they could be visualized and quantified in vivo or ex vivo using bioluminescence imaging.…”
mentioning
confidence: 99%
“…This is interesting, as the previous study on prostate cancer 7 indicated that b 2 -ARs expressed by tumour cells mediate the effects of behavioural stress. There are key differences between these studies, 7,8 namely, the sites of tumour injection (orthotopic injection vs. flank xenograft), the stimulus investigated (increased sympathetic innervation of the prostate vs. acute behavioural stress leading to increased circulating adrenaline), and the time course of the measured responses (resistance to apoptosis over a period of 6-72 h vs. tumour development over the course of 11 weeks).…”
mentioning
confidence: 99%
“…Activation of this signaling pathway increased therapy resistance and accelerated progression of prostate cancer in mice. 9 Earlier experiments in breast and ovarian cancer models demonstrated the importance of the tumor microenvironment (immune cells and angiogenesis) in mediating effects of stress on cancer progression. 6 Additional studies in mouse prostate cancer models will clarify whether these stressactivated mechanisms, identified in other cancers, operate in prostate cancer as well and whether anti-apoptotic signaling plays a leading role or is but one of several mechanisms through which stress influences prostate cancer.…”
mentioning
confidence: 99%
“…In fact, in 20% of prostate cancer patients, we observed increases of epinephrine over 1 nmol l 21 , a concentration that has been sufficient to activate the anti-apoptotic signaling pathway in tissue culture and in mouse prostates. 9 Several issues should be taken into account when clinical tests of inhibiting the ADRB2 pathway are planned. Is there a group of patients who consistently shows increased epinephrine levels, and are these patients characterized by nonproductive stress coping and anxiety?…”
mentioning
confidence: 99%